THE EXISTING POLICY ON PROSTITUTION IN INDONESIA: A RETROSPECTIVE EVALUATION - Suud, Mohammad (Universitas Wijaya Kusuma Surabaya, 2019)
This paper presents the policy on prostitution existing in the last ten years of the period of the New Order Regime. By using qualitative analysis, in the frame of rationality and coherence, author describes of the policy on prostitution and its results. The practice that was done by the government to tackle the prostitutes tended to be unjust, while the implication of the Indonesian Criminal Codeas the one of the national law saved a discrimination. The spirit of the law saved a moral weakness to endorse the creation of good life for Indonesian having the way of life Pancasila. Linked Â to the policy, the government tended frontally to tackle the prostitutes. As the policy made by the government was based on unhistorical and unsubstantial views, the governmentalÂ intervention to them has been more bringing problems than solutions. The inconsistency of the local governtments in managing the localization of prostitutes has compounded the problem. The governmental policy could not grasp the goals: rehabilitation and resosialization. The policy has empowered the institutionalization of prostitution and pimps. The government has been tacitly the institution of serving pimps.Â Key words: policy, prostitution, pimps